2005
DOI: 10.1021/ma035613l
|View full text |Cite
|
Sign up to set email alerts
|

Negatively Charged Ultrafine Black Particles of P(MMA-co-EGDMA) by Dispersion Polymerization for Electrophoretic Displays

Abstract: Polymeric particles ranging in diameter from 1 to 3.5 µm containing a black dye, Sudan black B, were prepared by dispersion polymerization in a methanol and water mixture. To control their electrophoretic mobility, a varying amount of charge control additives was added after first labeling them with a fluorescent moiety to trace their distribution by confocal laser microscopy. The particle size was found to be quite sensitive to both the change in polarity of the polymerization medium and the amount of polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 16 publications
2
27
0
Order By: Relevance
“…Generally, the swelling rate of monomer inside the particle increases as the polarity of polymerization media increases. 13,[29][30][31] Consequently, we infer that as the water ratio increases, DVB diffusion into PMMA particle becomes easier and has more uniform cross-link structure inside the particle. However, when the MeOH/water ratio is 100/0 with more than 3 wt% of DVB, DVB could not be infiltrated sufficiently inside the particle due to low polarity of the medium, and cross-link structure was formed near the particle surface, thereby swelling of MMA was refrained and small secondary particles was formed due to high cross-link density on the particle surface [ Figure 3(A)].…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the swelling rate of monomer inside the particle increases as the polarity of polymerization media increases. 13,[29][30][31] Consequently, we infer that as the water ratio increases, DVB diffusion into PMMA particle becomes easier and has more uniform cross-link structure inside the particle. However, when the MeOH/water ratio is 100/0 with more than 3 wt% of DVB, DVB could not be infiltrated sufficiently inside the particle due to low polarity of the medium, and cross-link structure was formed near the particle surface, thereby swelling of MMA was refrained and small secondary particles was formed due to high cross-link density on the particle surface [ Figure 3(A)].…”
Section: Resultsmentioning
confidence: 99%
“…The commonly used method currently is to encapsule the microspheres to prevent them from a large-scale flocculation [23,[27][28][29][30]. However, in the recent years, people try to disperse microspheres directly into the surfactant-containing apolar solvent to assemble the E-ink device [31][32][33][34], and in this situation the colloidal stability becomes much more important.…”
Section: Colloidal Stability In Surfactant-containing Apolar Solventmentioning
confidence: 99%
“…In recent years, people have tried to disperse microspheres directly into the apolar solvent to prepare E-ink [31][32][33][34]. This method is more convenient compared with microencapsulation method, but requires much better colloidal stability.…”
Section: Introductionmentioning
confidence: 99%
“…Though polymer microspheres have advantages like low density, easy fabrication and surface modification [22][23][24][25][26][27], inorganic pigments, especially for titanium dioxide (TiO 2 ) and carbon black (CB), were still studied for the actual applications in monochrome EPD because of its irreplaceable optical properties and the strong durability [28][29][30][31][32][33]. However, most of studies only reported the electrophoretic behavior of the single-particle suspension.…”
Section: Introductionmentioning
confidence: 99%